Dasar-Dasar Pemikiran Perlindungan Hak Kekayaan Intelektual - Darwance, Darwance; Yokotani, Yokotani; Anggita, Wenni (PROGRESIF: Jurnal Hukum, 2020)
Basically, humans are born with different intellectual abilities in processing their thougths and produce somethingfrom that thought. Therefore, it is important to provide protection for the results of thought through the intellectual property rights regime. However, in practice there are still many cases where the intellectual property of a person or agroup or a legal entity is used without prior permission. This juridical normative research examines fundamental thoughts for the protection of the results of one's thinking which is called intellectual property rights. There are several thoughts which become form the basis for protecting intellectual property rights; they are the natural right protection to reputation that has been built over a long time and quite high cost and also as a form of compensation and encouragement for people to create or find something.With the basic ideas behind the protection of IPR, the protection provided will be maximized, and the results of one's thinking will be more respected, both moral rights and economic rights